Research, development, and innovation agenda to strengthen the pineapple chain in Caloto, Cauca through smart agriculture - Mosquera Loboa, Karen Julieth (2026)
The pineapple production chain in Caloto, Cauca, faces structural challenges that limit its competitiveness, such as low educational attainment, limited technical assistance, and limited technology adoption. This study proposes a research, development and innovation (R+D+i) agenda to strengthen this chain through a mixed, applied, and exploratory methodological approach based on technological surveillance and competitive intelligence. Strategic projects were prioritized through a participatory process with stakeholders from the Quadruple Helix, highlighting initiatives in automation, precision agriculture, and waste recovery. The weighted evaluation allowed for prioritizing proposals based on their impact on productivity, costs, quality, sustainability, and dynamism. The results highlight opportunities to transform the local production model toward a more technologically advanced, sustainable, and resilient model, coordinating institutional, academic, and productive capacities and promoting technological appropriation through contextualized training and pilot projects.